Strategi Pengelolaan Keuangan Keluarga Prajurit TNI AL dalam Menghadapi Fluktuasi Ekonomi Global - Lawahery, Elphido T.M.; Pakpahan, Faurna Lusiana; Marsudi, Danang; Nurhartonosuro, Imam Munajat (Innovative: Journal Of Social Science Research, 2024)
Financial management of families of Indonesian Navy soldiers in the face of global economic fluctuations is an important subject to understand in the context of the complexity of military work which involves mobility and uncertainty. This study aims to explore financial management strategies, responses to global economic fluctuations, the role of financial education, and insurance coverage in the context of military families. The aim of this research is to understand in depth how families of Indonesian Navy soldiers manage their finances in the face of dynamic global economic changes. This research also aims to evaluate the effectiveness of financial strategies implemented by military families, as well as to highlight the importance of financial education and insurance coverage in maintaining financial stability. This research uses a qualitative approach with data collection techniques through in-depth interviews and observation. Research participants were family members of Indonesian Navy soldiers who were selected based on criteria of relevance to family financial management and their experience in dealing with global economic fluctuations. Primary and secondary data were analyzed using thematic coding to identify key patterns and themes that emerged from the interviews. The research results show that families of Indonesian Navy soldiers apply structured and adaptive financial management strategies. They create detailed monthly budgets, prioritize emergency savings, and manage investments carefully in response to global economic changes. Financial education is considered important in building financial literacy among family members, while insurance coverage provides financial security in the face of risks associated with military employment.